Effect of Training on Organic Waste Management in Neighborhoods of Pejanggik, Mataram, West Nusa Tenggara - Agus Supinganto; Suharmanto Suharmanto; Irwan Budiana; Raimunda Woga (Universitas Islam Bandung, 2022)
Garbage is solid waste consisting of organic and inorganic substances that outlived their usefulness and must be adequately managed to prevent environmental harm. The amount and types of waste are strongly influenced by the lifestyle and the type of materials we consume, and increasing household income cause an increase in the variety of waste generated. Handling and managing organic waste requires community involvement and successful household organic waste management, contributing significantly to the zero waste program. This study aims to measure the effect of waste management training on knowledge and principles of reducing, reusing, and recycling in waste management. The study was conducted from April to June 2021 in the neighborhoods around Pejanggik, Mataram village, West Nusa Tenggara province. It is a pre-experimental study involving 50 households to analyze the effects of the waste management training provided using a one-group pretest-posttest method. Before the training, knowledge and waste management principles were 22 of 50 respondents and 32 of 50 respondents, respectively. After the provision of training, the increase in knowledge and waste management principles reached 50 of 50 respondents. In conclusion, the training activity shows increased knowledge and waste management principles in households involved. Waste processing with reduce, reuse, and recycle principles can help overcome household waste problems and convert waste into products with increased economic value. Therefore, we recommend that periodic community-based waste management training involving households be held to overcome increased organic waste in households.